One Twin Too Many - Ashley and Kate-Mary; Adapted by Stine, Megan (New York A Parachute Press Book, 1998)
Oh, no! Mary-Kate and Ashley have to do history projects. But Ashley's found a way to make her project fun - she's partners with Pokey Valentine, the boy of her dreams, and it's the perfect way to get close to him. The only problem is, Pokey would rather get close to someone else - someone named Mary-Kate.
Include illustrations
Keywords: Twins -- Sisters -- Dating (Social customs)